The Effect of Benson's Relaxation on Blood Pressure in the Elderly in Hypertension Patients - Riyanto, Dwi Agung; Rochman, Dadang (Riviera Publishing, 2025)
Hypertension is a common health issue among the elderly and significantly impacts their quality of life. This study aims to evaluate the effectiveness of the Benson relaxation technique in reducing blood pressure in elderly individuals with hypertension at the Sajira Health Center. Using a pre-experimental method with a pretest-posttest design, measurements were taken before and after the intervention. Seventeen elderly participants with a history of hypertension were selected through purposive sampling. The results showed a significant reduction in blood pressure after the intervention. The average reduction in systolic blood pressure was 25.765 mmHg (SD = 13.917) and diastolic blood pressure was 14.118 mmHg (SD = 7.944). A paired sample t-test showed a significance value of p = 0.000, indicating a statistically significant effect of Benson relaxation in reducing blood pressure. Benson relaxation is effective in lowering blood pressure in the elderly and can be used as a non-pharmacological therapy. The Health Center can incorporate this technique into educational and promotive programs for hypertensive elderly individuals.